Pretransplantation assessment of BK virus seropositivity in kidney donors and recipients - Aswathi M. Nair; B. Arun; Feroz Aziz; Vipin Vishwanath; K. S. Deepak; K. Anagha; S. Santheep; S. Gladies Kamalam (Advances in Biomedical and Health Sciences, 2024)
Background: BK virus (BKV) is a member of the polyomavirus family. The determination of anti-BKV immunoglobulin G (IgG) antibody levels in kidney donors and recipients has been reported as a possible predictor of the risk of BK nephropathy. Allograft dysfunction is a significant risk factor. The main objective of this study was to address the high prevalence of renal failure due to BKV nephropathy in kidney transplant recipients. This investigation aims to determine whether donors and recipients of renal transplants had BKV IgG antibodies before transplantation. Methods: Blood samples were collected from 46 kidney transplant recipients and their corresponding 46 donors. An enzyme-linked immunosorbent assay was used to qualitatively analyze human BKV IgG. Results: Ninety-two participants, 46 kidney transplant donors, and 46 kidney transplant recipients, were analyzed. Pretransplantation anti-BKV antibody levels were higher in kidney transplant donors (73%) than in recipients (63%). Donors and recipients included in the study were grouped into seropositive and seronegative recipients, with the highest proportion of seropositive recipient-donor groups (48%) and the lowest percentages in the seronegative donor and seronegative recipient groups. Fifty-one percent of the participants were male and 49% were female. The age distribution of most subjects was >50 years old. Conclusion: BKV can cause kidney transplant rejection. Routine screening of transplant recipients and donors for BKV IgG seropositivity is recommended before renal transplantation. This can improve transplant outcomes and prevent rejection.